2022
DOI: 10.1590/fst.119721
|View full text |Cite
|
Sign up to set email alerts
|

Killer yeast isolated from some foods and its biological activity

Abstract: Seventy eight yeasts were isolated from different foodstuffs. Out of the seventy eight isolates four yeast species namely C. parapsilosis Q3, C. solani F8, C. versatilis J3 and K. jensenii H1 were selected to study their biological activity. The four strains termed as killer yeast by observing its activity against microorganisms. Killer yeasts secrete proteinaceous killer toxins lethal effect against some of Gram positive and negative bacteria, molds and yeasts. The antagonistic effect of the four killer yeast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Yeasts with antagonistic activity against other microorganisms are considered killer yeasts. They have been reported capable of secreting proteinaceous toxins against some pathogenic bacteria, molds and yeasts [55] [57] . The present finding is consistent with earlier research which found that nine yeast isolates were active against five different pathogens, including Bacillus spp, E. coli , Staphylococcus , Pseudomonas and Klebsiella [22] , [33] .…”
Section: Resultsmentioning
confidence: 99%
“…Yeasts with antagonistic activity against other microorganisms are considered killer yeasts. They have been reported capable of secreting proteinaceous toxins against some pathogenic bacteria, molds and yeasts [55] [57] . The present finding is consistent with earlier research which found that nine yeast isolates were active against five different pathogens, including Bacillus spp, E. coli , Staphylococcus , Pseudomonas and Klebsiella [22] , [33] .…”
Section: Resultsmentioning
confidence: 99%